SoCFaSe : in quest for fast and secure SoC architectures - Gupta, Naina (Nanyang Technological University, 2023)
Over the past few years, Internet of Things (IoT) has gained a lot of attention. It is mainly due to significant improvements in technology, available processing power and efficiency. This allowed for the deployment of Artificial Intelligence (AI) techniques on these devices. The billions of smart devices connected worldwide nowadays are embedded with commodity sensors, real-time analysis and decision making. This evolution has resulted in IoT devices becoming intelligent, smart, and more responsive. Even though this fusion of physical and digital universe has proved to be beneficial in multiple sectors such as healthcare, autonomous driving, smart home, etc. Such a growth has also led to many security challenges especially with the rise in side-channel attack possibilities. As these devices collect a lot of data and the decision-making process is data driven; security of such devices becomes a necessity for safety-critical and time-critical applications.